2008
DOI: 10.1080/10910340802067395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Disc Dressing Effects on Grinding Performance—part 1: Simulation of the Disc Dressed Wheel Surface

Abstract: & This article is in two parts describing the analysis and simulation of the disc dressing process and its effect on grinding performance. This part is concerned with the generation of the wheel surface by a diamond disc dresser. A new stochastic model of the prediction of wheel topography by diamond disc dresser is developed. It predicts the number of active grains per unit area and average slope of grains of the alumina grinding wheel. This model is based on the fracture of grits and it considers the kinemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In the previous papers by the author et al [7,8], a new stochastic model of the prediction of wheel topography by diamond disc dresser was developed. Then the effects of a disc dressing parameter that affects the wheel topography, specific energy, and workpiece surface roughness were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous papers by the author et al [7,8], a new stochastic model of the prediction of wheel topography by diamond disc dresser was developed. Then the effects of a disc dressing parameter that affects the wheel topography, specific energy, and workpiece surface roughness were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In a study [19], Pamer studied also the influence of the dressing parameters on the topography of grinding wheel. Besides, many studies have been done to understand the influence of the dressing conditions on quality and accuracy of grinding process [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Cebalq [5] found that the different combinations between the dressing mode, dressing conditions, and the grinding wheel specification lead to different inter-grit spacing between the abrasive grits of the grinding-wheel cutting surface and, as a result, different response variables of the grinding process (equivalent grinding thickness, specific metal removal rate, roughness of the grinding-wheel cutting surface, roughness of the ground surface, etc.). Baseri et al [6] and [7] and Baseri [8], Wegener et al [9] and Palmer et al [10] proved that the grindingwheel topography and the conditions under which it is prepared have a profound influence upon the grinding performance, defined by the grinding forces, the power consumption, the cutting zone temperature, the radial wear of the wheel and also the surface finish of the workpiece. Chen et al [11] found that a satisfied and stable grinding process can be controlled in real-time by means of utilizing the combination of optimal parameters, such as spindle speed, effective pack density, and the cutting space of abrasive grits.…”
Section: Introductionmentioning
confidence: 99%